Latent growth curve modelling of Portuguese life satisfaction trajectories - Salgueiro, M.F. (International Journal of Academic Research, 2010)
This paper proposes using latent growth curve models (LGCMs) to model life satisfaction growth trajectories. Portuguese data from the European Community Household Panel (ECHP) are used. The eight waves for which the data are available (years 1994 to 2001) are considered. The four life satisfaction variables under analysis include satisfaction with: work or main activity, financial situation, housing situation, and amount of leisure time. In order to explain growth trajectories, eight possible determinants of life satisfaction are included in the model as time-invariant covariates: age, gender, education, marital status, perceived health status, income, number of working hours and job status